Early Tranexamic Acid in Intracerebral Hemorrhage: A Meta-Analysis of Randomized Controlled Trials - Jiao, Xu; Li, Mingfei; Li, Lulu; Hu, Xinyu; Guo, Xiaohui; Lu, Yun (Frontiers in Neurology, 2021)
Objective: Intracranial hemorrhage (ICH) is a common complication of traumatic brain, in which tranexamic acid has been recommended as an additional therapy to prevent a second bleeding. However, the effect of early administration of tranexamic acid for ICH patients remains controversial. Methods: A systematic search was performed in Cochrane Library, Medline, Embase, and Web of Science. Poor outcome refers to significant haemorrhage growth, new intracranial haemorrhage, new focal cerebral ischaemic lesions, the need for neurosurgery, or death. Study heterogeneity and publication bias were estimated. Results: Seven randomized controlled trials involving 3192 participants were included in our meta-analysis. Tranexamic acid administration in ICH patients was associated with better outcomes of hematoma expansion (odd ratios [OR] 0.79; 95% confidence interval (CI) CI, 0.67–0.93; I2 = 0%; P = 0.006) and growth of hemorrhagic lesions (weighted mean difference [WMD], -1.97 ml; 95% CI, -2.94 to -1.00; I2 = 14%; P < 0.001) than the placebo. No difference was found between the mortality, poor outcome, neurosurgical intervention, new bleeding, and the duration of hospital stay. Moreover, no publication bias was found. Conclusion: Our analysis reveals that the early treatment with tranexamic acid can significantly reduce the incidence of hematoma expansion and the volume of hemorrhagic lesion, but does not exert considerable effects on mortality, poor outcome, neurosurgery, rebleeding, and the duration of stay.